SIYASAH ANALYSIS OF APPLICATION LICENSING TIKTOK SHOP ACCORDING TO THE PERMENDAGRI NUMBER 31 OF 2023 - Ahmad Sahdan Pasaribu; Akmaluddin Syahputra (PT. Radja Intercontinental Publishing, 2024)
This writing contains various forms of problems which are used as complaints experienced by several people regarding regulations or policies regarding transaction permits in the TikTok Shop social media application as the current digitalization of buying and selling. The formulation of the problem in this research is first how the provisions of Permedagri No. 31 of 2023 regarding the social media application TikTok Shop which facilitates payment transactions for consumers in commerce via electronic systems and secondly, what is the view of fiqh siyasah regarding the TikTok application which has facilitated payment transactions for consumers via electronic systems. The author uses a normative juridical approach to show that written regulations are in the form of laws. Research must be based on data or correspondence that supports research to be more systematic and not just engineering in research. And it is more accurate that research is carried out carefully and with full consideration in achieving a goal in the research.